The Evolution of Sustainable Business Practices: A Bibliometric Study on Corporate Social Responsibility and Green Marketing - Loso Judijanto; Adi Suroso; Achmad Choerudin (North Press, 2024)
This bibliometric study explores the evolution and integration of Corporate Social Responsibility (CSR) and Green Marketing within sustainable business practices over the past two decades. Utilizing data from major databases such as Web of Science and Scopus, the research employs keyword co-occurrence and citation analysis to map the thematic landscape and identify research hotspots and trends. Findings highlight